Siberian Yupik Names for Birds: What Can Bird Names Tell Us about Language and Knowledge Transitions? - Krupnik, Igor (Études Inuit Studies)

(untitled) (Centre interuniversitaire d’études et de recherches autochtones (CIÉRA), 2017)
This article analyzes the list of Siberian Yupik names for birds from Chukotka, Russia, from the unpublished “Dictionary of Traditional Subsistence Terminology of the Asiatic Yupik Eskimo” (n.d., [2010]), produced by the late Russian biologist Lyudmila Bogoslovskaya and Yupik language expert Lyudmila Ainana. It compares Bogoslovskaya and Ainana’s list against other lists of Indigenous bird names compiled in Chukotka and among the nearby Native Alaskan groups in the Bering Strait area, and biological (Linnaean) bird nomenclatures for the same region. The sequence of collected Yupik bird name lists from the 1930s to the early 2000s reveals a strong correlation to the advancing language and knowledge shift, as the Chukotka Yupik were increasingly driven to bilingualism by the Russian-dominated speech environment, media, and school system. By the time ornithologists and linguists compiled the first Native lists of bird names, the Yupik in Chukotka had already lost certain layers of their traditional bird taxonomy, but some of its elements may be construed. As the loss of traditional names for birds continues, the Yupik actively borrow Russian terms (or English, in Alaska) to describe many bird species they encounter in their environment.